State of the art - interventional pulmonology - Wahidi, Momen M.; Herth, Felix; Chen, Alexander; Cheng, George; Yarmus, Lonny (Chest, 2020)
Interventional pulmonology (IP) has evolved over the past decade from an obscure subspecialty in pulmonary medicine to a recognized discipline offering advanced consultative and procedural services to patients with thoracic malignancy, anatomic airway disease, and pleural disease. Innovative interventions are now also available for diseases not traditionally treated procedurally, such as asthma and emphysema. The IP field has established certification examinations and training standards for IP training programs in an effort to enhance training quality and ensure competency. Validating new technology and proving its cost-effectiveness and effect on patient outcomes present the biggest challenge to IP as the health-care environment marches toward value-based health care. High-quality research is now thriving in IP and promises to elevate its practice into patient-centric evidence-based care.